Answers

2015-06-05T22:44:58+08:00

This Is a Certified Answer

×
Certified answers contain reliable, trustworthy information vouched for by a hand-picked team of experts. Brainly has millions of high quality answers, all of them carefully moderated by our most trusted community members, but certified answers are the finest of the finest.
In an arithmetic sequence:
a_2-a_1=a_3-a_2=a_4-a_3=,...,=a_n-a_{n-1}=d
So:
3k-11-(k+2)=k+2-(5k-3) \\ 2k-13=-4k+5 \\ 6k=18 \\ k=3
14 3 14
how did you get that?
In an arithmetic sequence, the difference between two consecutive terms is the same so the given terms must satisfy that as well, so when we subtract the first term from the second, we must have the same difference when we subtract the second term from the third.
thanks for these .